Addressing race in economics: Teaching to Transgress - Venkatesan, Madhavi (Contemporary justice review, 2022)
In economics, race is often used as an explanatory variable. However, context for observed correlations is not often discussed and when it is, the discussion truncates history to the 1960’s and the era of the Civil Rights movement. The latter is consistent with the projection that regulation has limited or eliminated racial disparity and therefore, other factors, cultural and individual, account for observed economic status. However, the evidence to counter this is observable. For example, to the extent that the intergenerational impact of oppression is factored into economic analysis, and qualitative attributes such as anxiety and depression are incorporated into the explanation for the persistence of poverty, social norms rather than race are revealed to be the contributors to present period variations in economic outcomes. Inspired by bell hooks’ Teaching to Transgress we address how the teaching of economics has contributed to the normalization of racialized discrimination. We then address how the economics curriculum can be used as a tool to facilitate racial equity. The discussion adds value to the discourse on race by addressing how the commoditization of teaching has eliminated classroom engagement and critical thinking and concludes with the value of transgression in addressing social justice in economics.